1996
DOI: 10.2331/fishsci.62.1
|View full text |Cite
|
Sign up to set email alerts
|

Age and Growth of Pacific Saurey <i>Cololabis saira</i> (Brevoort) in the Western North Pacific Ocean Estimated from Daily Otolith Growth Increments

Abstract: Growth of Pacific saury Cololabis saira (Brevoort) inhabiting the western North Pacific was studied based on counting daily growth increments with a scanning electron microscope (SEM). The small-size group (knob length: 200-240 mm), medium-size group (knob length: 240-280 mm) and large size group (knob length: >280 mm) showed increments of 256•}26.0 (S.D.), 405•}76.1 and 566•}48.2, respectively. Based on daily growth increment formation, we determined that the ages of the 3 groups were about 8, 13, and 19 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 2 publications
1
28
0
Order By: Relevance
“…On the other hand, Watanabe and Kuji [12] showed that the microincrements in the otolith [13] are daily growth increments in rearing experiments. Based on their report, the age (in days) of Pacific saury can be assessed and growth analysis can be performed [10,11,[14][15][16][17][18]. However, the number of daily otolith rings in the hyaline zone cannot generally be counted [10,11], and so, because it was difficult to calculate the total number of daily rings in one-year fish with hyaline zones, we could not determine the hatch date.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Watanabe and Kuji [12] showed that the microincrements in the otolith [13] are daily growth increments in rearing experiments. Based on their report, the age (in days) of Pacific saury can be assessed and growth analysis can be performed [10,11,[14][15][16][17][18]. However, the number of daily otolith rings in the hyaline zone cannot generally be counted [10,11], and so, because it was difficult to calculate the total number of daily rings in one-year fish with hyaline zones, we could not determine the hatch date.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their report, the age (in days) of Pacific saury can be assessed and growth analysis can be performed [10,11,[14][15][16][17][18]. However, the number of daily otolith rings in the hyaline zone cannot generally be counted [10,11], and so, because it was difficult to calculate the total number of daily rings in one-year fish with hyaline zones, we could not determine the hatch date. Kurita et al [18] counted the number and measured the widths of otolith daily rings of age-zero fish that had not yet formed a hyaline zone, and found that daily growth increments were widest after hatching and subsequently narrowed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger saury (>280 mm) hatched from autumn to winter in the JARPN II survey period (Suyama et al, 1996) are mature, and adult size saury have a higher caloric value compared to other prey, suggesting the minke whales feed on the highly nutritious saury later in the season when mature saury are distributed in the subarctic region.…”
Section: What Determines the Diet Of Whales In Spatiotemporal Scale?mentioning
confidence: 99%
“…In the western Pacific, saury reach a length of 30 cm in 1 year (Watanabe et al, 1988). Their life span has been estimated to be 1.5-2.0 years (Suyama et al, 1996). The fishing grounds in the Oyashio region in autumn vary depending on the location of the Oyashio and warm core rings that originate in the Kuroshio and Tsugaru Warm Current.…”
Section: Mackerel Including Chub (S Japonicus) and Spotted Mackerelmentioning
confidence: 99%